2019
DOI: 10.3390/jcm8101504
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Usefulness of a Serious Game to Raise Awareness about Mental Health Problems in a Sample of High School and University Students: Relationship with Familiarity and Time Spent Playing Video Games

Abstract: Background: One of the main challenges in the field of mental health today is the stigma towards individuals who have psychological disorders. Aims: This study aims to analyse the usefulness of applying a serious game developed for the purpose of raising awareness among students about mental health problems and analyse whether its usefulness can be influenced by the type of video games or the time that students usually devote to playing with this type of entertainment. Method: The serious game introduces four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…The socialization of video games is a reality established in the young population they live in every day. Numerous research studies conducted on college students have shown how video games' abuse can lead to mental disorders (Cangas et al, 2019;Hsieh, Hsiao, Yang, Liu, & Yen, 2018;King, Delfabbro, Zwaans, & Kaptsis, 2013;Ni, Yan, Chen, & Liu, 2009) and impact daily tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The socialization of video games is a reality established in the young population they live in every day. Numerous research studies conducted on college students have shown how video games' abuse can lead to mental disorders (Cangas et al, 2019;Hsieh, Hsiao, Yang, Liu, & Yen, 2018;King, Delfabbro, Zwaans, & Kaptsis, 2013;Ni, Yan, Chen, & Liu, 2009) and impact daily tasks.…”
Section: Discussionmentioning
confidence: 99%
“…For the adolescent community, playful experiences have not gone unnoticed. This methodological strategy has been used in different settings such as health and well-being, for example to involve adolescents in adopting healthier lifestyle behaviors [13]; socio-cultural to raise awareness of the proper use of social networks [14] or therapeutic as gamma applications of mental health [15]. Finally, in the educational field, the use of gamification [16], educational games [17], and playful strategies such as modeling through applications with a game interface such as Classdojo or Classcraft [18] are being studied as learning tools that provide an attractive and motivating approach due to their ability to teach and reinforce curricular content and skills.…”
Section: Adolescents' Motivations For Video Gamesmentioning
confidence: 99%
“…While these strategies have been implemented in different countries ( 28 30 ) and have led to decreasing stigma ( 31 , 32 ) and promoting positive perceptions of psychiatric patients among students and professionals ( 33 , 34 ), their implementation in virtual learning spaces is recent, particularly for university students ( 35 ). Several authors highlight the advantages of using multimedia resources, for instance audiovisual educational resources with standardized patients ( 36 , 37 ), E-contact with psychiatric patients ( 38 ), and even the implementation of educational videogames ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%